Evaluation of Riboflavin Transporters as Targets for Drug Delivery and Theranostics - Bartmann, Lisa; Schumacher, David; von Stillfried, Saskia; Sternkopf, Marieke; Alampour-Rajabi, Setareh; van Zandvoort, Marc A. M. J.; Kiessling, Fabian; Wu, Zhuojun (Frontiers in Pharmacology, 2019)
The retention and cellular internalization of drug delivery systems and theranostics for cancer therapy can be improved by targeting molecules. Since an increased uptake of riboflavin was reported for various cancers, riboflavin and its derivatives may be promising binding moieties to trigger internalization via the riboflavin transporters (RFVT) 1, 2, and 3. Riboflavin is a vitamin with pivotal role in energy metabolism and indispensable for cellular growth. In previous preclinical studies on mice, we showed the target-specific accumulation of riboflavin-functionalized nanocarriers in cancer cells. Although the uptake mechanism of riboflavin has been studied for over a decade, little is known about the riboflavin transporters and their expression on cancer cells, tumor stroma and healthy tissues. Furthermore, evidence is lacking concerning the representativeness of the preclinical findings to the situation in humans. In this study, we investigated the expression pattern of riboflavin transporters in human squamous cell carcinoma (SCC), melanoma and luminal A breast cancer samples, as well as in healthy skin, breast, aorta and kidney tissues. Low constitutive expression levels of RFVT1-3 were found on all healthy tissues, while RFVT2 and 3 were significantly overexpressed in melanoma, RFVT1 and 3 in luminal A breast cancer and RFVT1-3 in SCC. Correspondingly, the SCC cell line A431 was highly positive for all RFVTs, thus qualifying as suitable in vitro model. In contrast, activated endothelial cells (HUVEC) only presented with a strong expression of RFVT2, and HK2 kidney cells only with a low constitutive expression of RFVT1-3. Functional in vitro studies on A431 and HK2 cells using confocal microscopy showed that riboflavin uptake is mostly ATP dependent and primarily driven by endocytosis. Furthermore, riboflavin is partially trafficked to the mitochondria. Riboflavin uptake and trafficking was significantly higher in A431 than in healthy kidney cells. Thus, this manuscript supports the hypothesis that addressing the riboflavin internalization pathway may be highly valuable for tumor targeted drug delivery.